2019
DOI: 10.1097/shk.0000000000001314
|View full text |Cite
|
Sign up to set email alerts
|

Function is Dissociated From Activation-Related Immunophenotype on Phagocytes From Patients With SIRS/Sepsis Syndrome

Abstract: Sepsis is a life-threatening condition associated with failure of at least one organ in the presence of infection. Along with SIRS, the acute systemic inflammatory syndrome without documented infection, sepsis represents a main health problem in intensive care units around the world. Hypercytokinemia and overexpression of activation-markers on leukocytes are frequently reported in SIRS/sepsis. Leukocyte functions including antibody mediated-phagocytosis, pathogen recognition, and migration appear to be disable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
8
1
Order By: Relevance
“…Contrary to other reports [17,18], the total numbers of circulating monocytes remain unchanged in our study between septic (n = 36) and non-septic (n = 40) ICU patients (Figure 2A, right panel). However, we could observe alterations in the composition of monocyte populations dependent on the presence of sepsis.…”
Section: Alterations In the Composition Of Circulating Monocyte Populcontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to other reports [17,18], the total numbers of circulating monocytes remain unchanged in our study between septic (n = 36) and non-septic (n = 40) ICU patients (Figure 2A, right panel). However, we could observe alterations in the composition of monocyte populations dependent on the presence of sepsis.…”
Section: Alterations In the Composition Of Circulating Monocyte Populcontrasting
confidence: 99%
“…Several studies reported increased numbers of circulating monocytes in patients with diagnosed sepsis [17,18], including alterations of the monocyte subset distribution [22]. We herein investigated the abundance and phenotype of different monocyte subpopulations in a prospective patient study, including 54 healthy controls (HC), 42 standard care patients (SC) with confirmed infection, and 76 critically ill patients upon admission to the intensive care unit (ICU) ( Table 1).…”
Section: Alterations In the Composition Of Circulating Monocyte Populmentioning
confidence: 99%
See 1 more Smart Citation
“…Many other life-threatening, noninfectious causes such as shock states, trauma or ischemia–reperfusion injury are associated with systemic inflammatory response syndrome (SIRS) ( 78 ). Although the etiology of these pathologies is different, human SIRS and sepsis share similar patterns of cytokine expression ( 79 ). Like in sepsis, this robust inflammatory storm is also associated with the extensive formation of cell debris arising from apoptosis ( 80 ) and necroptosis ( 81 ) of many different cell types, which needs to be cleared by phagocytes.…”
Section: Cytokine-mediated Regulation Of Phagocytosis In Sepsismentioning
confidence: 99%
“…CD16 and CD32 on monocytes are less expressed on adults than in neonates, and the CD64 expression on granulocytes is higher in neonates than adults (15). Also, it has been reported that after IVIg treatment, the FcγR expression changes on effector cells in mice (16,17).…”
Section: Introductionmentioning
confidence: 99%